Предмет: Алгебра,
автор: olesagood011
(2х+0,3)-(3х-3)=5
2(х-3)-5(х-7)=5-(х+6)
решите пожалуйста
Ответы
Автор ответа:
1
6х-2.7 =5
6х=5+2.7
6х=7.7
Х=1.2
6х=5+2.7
6х=7.7
Х=1.2
Автор ответа:
1
1)(2х+0,3)-(3х-3)=5
2x+0.3-3x+3-5=0
-1x-1.7=0
x=-1.7
2) 2(х-3)-5(х-7)=5-(х+6)
2x-6-5x+35=5-x-6
-2x=-30
x=15
2x+0.3-3x+3-5=0
-1x-1.7=0
x=-1.7
2) 2(х-3)-5(х-7)=5-(х+6)
2x-6-5x+35=5-x-6
-2x=-30
x=15
Похожие вопросы
Предмет: Химия,
автор: pavel75511
Предмет: Биология,
автор: ksenia1151
Предмет: Математика,
автор: bananandhabibka2009
Предмет: Алгебра,
автор: KalaschnikovaNastya1
Предмет: Алгебра,
автор: 777777732